Linking 'data silos' to investigate anaemia among Aboriginal and Torres Strait Islander mothers and children in Far North Queensland - Dympna Leonard; Petra Buettner; Fintan Thompson; Maria Makrides; Robyn McDermott (Elsevier, 2018)
Abstract Objective: Data collection 'silos' can be linked for health research. Anaemia in early childhood is a long‐recognised health issue in remote Aboriginal communities of the Northern Territory and Western Australia, but information is lacking for Queensland. The objective of this work was to compile existing information from health and education data collections to investigate anaemia among Aboriginal and Torres Strait Islander mothers and their children in Far North Queensland. Methods: Data mapping identified four health data collections and one education data collection holding relevant information. Data Custodians' approval was secured for release of linked de‐identified information. Results: Approval processes and preparation of the dataset for release took 23 months. Birth information was obtained for 2,205 mother-child pairs where the Aboriginal and/or Torres Strait Islander child was born in Far North Queensland between 2006 and 2010. Pathology information from before/during pregnancy was obtained for 2,126 mothers (96.4%), growth and haemoglobin information for 982 children (44.5%), and childhood development indicators at school entry for 963 children (43.7%). Conclusion: Linking existing information 'silos' enables research into key public health issues. Implications for public health: Information linkage is particularly valuable in respect of vulnerable populations including rural and remote Aboriginal and Torres Strait Islander peoples.